Asymptotic behavior of inexact infinite products of nonexpansive mappings - REICH, Simeon; ZASLAVSKI, Alexander J. (Studia Universitatis Babeș-Bolyai Mathematica, 2021)
We analyze the asymptotic behavior of inexact infinite products of non- expansive mappings, which take a nonempty closed subset of a complete metric space into the space, in the case where the errors are sufficiently small. Mathematics Subject Classification (2010): 47H09, 47H10, 54E50.